AB0589 Non-Infectious Aortitis: Still an Underdiagnosed Entity. Report of 32 Cases from A Single Center. (10th June 2014) - Loricera, J.; Blanco, R.; Carril, J.M.; Martínez-Rodríguez, I.; Hernández, J.L.; Canga, A.; Peirό, E.; Alonso-Gutiérrez, J.; Calvo-Río, V.; Ortiz-Sanjuán, F.; Santos-Gόmez, M.; Mata, C.; et al.
Abstract : Background: Non infectious aortitis may present as an idiopathic isolated condition or associated with a wide spectrum of diseases. Aortitis often presents with nonspecific symptoms leading in many cases to an inappropriate diagnostic delay. Objectives: Our aim was to analyze the clinical features and outcome of patients with aortitis in order to improve the diagnosis of this entity. Methods: We studied 32 patients (22 women and 10 men) with a mean age of 68 years (range, 45-87 years) at the time of diagnosis. The median interval from the clinical onset to the diagnosis was 21 months. F18-FDG PET scan was the usual radiological method for diagnosing aortitis. Results: The underlying conditions were: giant cell arteritis (n=13 cases); isolated polymyalgia rheumatica (PMR) (n=11); Sjögren syndrome (n=2), Takayasu arteritis (TakA) (n=1); sarcoidosis (n=1), ulcerative colitis (n=1), psoriatic arthritis (n=1), and idiopathic aortitis (n=2). The most common clinical manifestations at diagnosis were: PMR features, often atypical in the clinical presentation (n=23 patients, 72%); diffuse lower limb pain (n=16 patients, 50%); constitutional symptoms (n=12 patients, 37%), inflammatory back pain (n=9 patients, 28%) and fever (n=7 patients, 22%). In most of the cases, serum acute phase reactants were increased, with a median erythrocyte sedimentation rate of 46 mm/1st hour and a median serum C-reactive protein of 1.5 mg/dL. Conclusions: In conclusion, aortitis is not an uncommon disease. The diagnosis is often a challenge for the clinician. The presence of PMR features, in particular when they are atypical, unexplained low back or limb pain, constitutional symptoms along with increased acute phase reactants should be considered "red flags" to suspect the presence of an underlying aortitis. Acknowledgements: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2978